Time interval integration with a chromosomal translocation affecting 7q31 - Garcia-Bellido, P; Benitez-Burraco, A (Universidad de Malaga, 2013)
How exactly auditory stimulation initiates language comprehension is still unknown. Some lines of research point to the possible involvement of sub-cortical and cortical circuits, particularly through a functional network comprising the striatum-thalamus-cortex and cerebellum, in which FOXP2 is expressed. This network is thought to support the production and perception of time intervals. In order to evaluate if deficient perception and timing of short time interval words (SIW) in the range of 20 to 200 ms - crucial for timing correctly the integration of long time interval words (LIW) above 200ms - can increase the degree of difficulty in comprehension, we study here a 11 year old subject, A, with a break at some point in the 7q31 region, where FOXP2 is located. Using an audio-visual test with linguistically relevant SIWs contained in basic grammatical constructions and comparing A’s difficulty score with that of a 4-11 year old normal population (NP) and that of a control matched in age, sex, schooling, language and socioeconomic background, it was found that A scored higher than a 6 year old but lower than a 7 year old. Subject A’s anomalous degree of difficulty for specific constructions with SIWs is not consistent with these ages’ performance, but rather suggests an anomalous impairment in perceiving and timing SIWs without which timing correctly the integration of LIWs might be disrupted.